2013
DOI: 10.1103/physrevd.87.014502
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Lüscher formula in multichannel baryon-meson scattering

Abstract: Lüscher's formula relates the elastic scattering phase shifts to the two-particle energy levels in a finite cubic box. The original formula was obtained for elastic scattering of two massive spinless particles in the center of mass frame. In this paper, we consider the case for the scattering of a spin 1/2 particle with a spinless particle in multi-channel scattering. A generalized relation between the energy of two particle system and the scattering matrix elements is established. We first obtain this relatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 64 publications
3
57
0
Order By: Relevance
“…Correspondingly the notation SP co (S − , N + ) means the SP of S − coexisting with N + since S − is the lower energy state. The bistable MMQSs observed in this paper agree with the dynamic study of nonequilibrium QPT [13,16]. In the area (yellow) between the line of U = 30 and curve g c+ we have only the single NP of N + with full population inversion, which induced by the nonlinear interaction is a new observation.…”
Section: Bistability and Atomic Population Inversionsupporting
confidence: 75%
See 3 more Smart Citations
“…Correspondingly the notation SP co (S − , N + ) means the SP of S − coexisting with N + since S − is the lower energy state. The bistable MMQSs observed in this paper agree with the dynamic study of nonequilibrium QPT [13,16]. In the area (yellow) between the line of U = 30 and curve g c+ we have only the single NP of N + with full population inversion, which induced by the nonlinear interaction is a new observation.…”
Section: Bistability and Atomic Population Inversionsupporting
confidence: 75%
“…It has been shown that the nonlinear interaction, indeed, results in dynamically unstable phase [16]. Most recently the coexistence of NP and SP was found in the nonequilibrium QPT with time-dependent atom-field coupling [12,16] based on the numerical simulation of zero-points of the energy functional. In order to understand the mechanism of multiphase coexistence we revisit the generalized Dicke model of BEC-cavity experiment [14,17] with nonlinear interaction J z a † a in the whole region of experimental parameters to reveal the bistable NPs as well as the coexistence of NP and SP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In case when only two-particle coupled channels appear, one can make use of the coupled-channel Lüscher equation [2][3][4][5][6][7][8][9] and fit a simple pole parameterization for the multi-channel K-matrix elements to the measured energy spectrum in the finite volume [10][11][12]. A more sophisticated parameterization of the K-matrix elements, which is applicable in a wider range of the energies, can be obtained using unitarized chiral perturbation theory (ChPT) [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%